Can deep freezing maintain the quality of two different Iberian pork products over a long storage period? - Ainhoa Sarmiento-García; Beatriz Martínez; Begoña Rubio; Juan-José García-García; Ceferina Vieira (Italian Journal of Animal Science)
To assess whether prolonged frozen storage preserves the properties of two deep-frozen Iberian pork products (sirloin and ‘picadillo’), the technological, microbiological, and sensory characteristics of both products (n = 32) were evaluated at zero time in the fresh product, and after 12, 18 and 24 months of storage at −20 °C after deep-freezing at −80 °C for 50 min after thawing. Frozen storage time affected microbial quality with different trends depending on the microbial count and the product assessed. An increase in pH value and water holding capacity (p < 0.05) was observed in sirloin at the end of storage, while ‘picadillo’ showed the opposite trend. In the sensory analysis, panellists recorded a decrease in value (p < 0.05) as storage time increased for both products, with more evident changes observed in the ‘picadillo’. The higher fat content and the greater surface area of the minced meat could be responsible for the most evident differences. Although ‘picadillo’ was more sensitive to storage, the results suggest frozen storage for up to 24 months of deep-frozen Iberian meat products could preserve their quality. Extended storage of up to 24 months could be a suitable strategy for preserving the high quality of Iberian pork.